IMPACT OF TREATMENT OF DIABETIC MACULAR EDEMA ON VISUAL IMPAIRMENT IN PEOPLE WITH TYPE 2 DIABETES MELLITUS: A COMPREHENSIVE SYSTEMATIC REVIEW AND METAAANALYSIST STUDY - Yovita,; Setiohadji, Bambang (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Diabetic retinopathy (DR) and diabetic macular edema (DME) are among the most significant and disabling chronic complications of diabetes mellitus. DME is an important cause of severe vision loss in type 2 diabetes. Hyperpermeability of retinal blood vessels and subsequent formation of edema and hard exudates are the key clinical features. Method: This systematic review and meta-analysis, conducted following PRISMA guidelines and employing the PICO format, aim to explore about impact of treatment of diabetic macular edema on visual impairment in people with type 2 diabetes mellitus, focusing on treatment, complications, and prognosis. Inclusion criteria encompass diverse study designs (RCTs, observational, quasi-experimental, and case-control studies) investigating impact of treatment of diabetic macular edema on visual impairment in people with type 2 diabetes mellitus among treatment, complications, and prognosis, while exclusion criteria filter out studies lacking relevance to impact of treatment of diabetic macular edema on visual impairment in people with type 2 diabetes mellitus. Result: After conducting three levels of screening, the results of our search in Pubmed get 6 articles, whereas the results of our search on SageJournal get 42 articles, on Lancet 21, and on Scient direct get 60 articles. Records remove before screening are 91, so we get 78 articles for screening. After we screened based on record exclude, we compiled a total of 10 papers. We included four research that met the criteria.  Conclusion: There is a particularly robust response to anti-VEGF therapy in both groups when glycemic control is optimized, highlighting the critical importance of communication between the physicians managing the DME and those managing systemic diabetes control. Improving our understanding of the factors that contribute to anti-VEGF response for DME therapy may help to enhance DME treatment outcomes, particularly through the concerted coordinated efforts of the treating retina specialist and the endocrinologist or primary care physician.